Non-lamellar lipid liquid crystalline nanoparticles: A smart platform for nanomedicine applications - Fornasier, Marco; Murgia, Sergio (Frontiers in Soft Matter, 2023)
The increased interest of the scientific community in lipid nanoparticles has pushed the boundaries of personal medicine and drug delivery. The focus has been set on vesicular nanocarriers, as their structure and functionalities have been well described, but the application of their non-lamellar counterparts, cubosomes and hexosomes, has shown their potency as drug carriers. In addition, the sponge phase dispersion (L3, an intermediate between the lamellar and the bicontinuous cubic) has also been proved effective for the encapsulation of large macromolecules. Their physicochemical characterization has improved in the past decades due to the investigations conducted at high-power synchrotron facilities and the application of surface-sensitive techniques, discovering new connections between physical parameters and biological performance. Several administration routes of cubosomes and hexosomes have been studied, such as intravenous, dermal, transdermal, and oral, to evaluate their cytotoxicity and distribution in biological media. This review aims to summarize the challenges and recent achievements of cubosomes, hexosomes, and sponge nanoparticles as suitable carriers for the administration of bioactives.